Case Report: A novel CIITA mutation causing MHC class II deficiency: first reported case in Morocco - Kattra, Aziza Bachir; Ailal, Fatima; Benhsaien, Ibtihal; Fahi, Mohammed; Drissi Bourhanbour, Asmaa; Elamine, Ahamada; Aadam, Zahra; Errami, Abderrahmane; Bousfiha, Ahmed Aziz; El Bakkouri, Jalila (Frontiers in Immunology, 2025)
Major histocompatibility complex class II (MHC II) deficiency (bare lymphocyte syndrome type II) is an autosomal-recessive combined immunodeficiency caused by pathogenic variants in the transcriptional regulators CIITA, RFXANK, RFX5, or RFXAP. While RFXANK founder mutations predominate in North Africa, CIITA-related disease is extremely rare. We report two siblings from a consanguineous Moroccan family with the classic early-infancy phenotype. The elder sister developed recurrent febrile rashes, oral candidiasis, and locoregional BCGitis with acid-fast bacilli in granulomas, followed by progressive respiratory failure and fatal cytomegalovirus pneumonitis despite antiviral therapy; immunology showed profound CD4+ lymphopenia with CD4/CD8 inversion, near-absent HLA-DR on B cells, undetectable IgG/IgA, and elevated IgM. The proband, identified during family follow-up, had recurrent mucocutaneous infections, marked CD4+ lymphopenia with CD4/CD8 inversion, and near-absent HLA-DR on B cells; he was started on monthly intravenous immunoglobulin and trimethoprim–sulfamethoxazole prophylaxis. Targeted next-generation sequencing revealed a novel homozygous nonsense CIITA variant (c.1615C>T; p.R539*), predicted to truncate the GTP-binding domain, abolish downstream leucine-rich repeats, and undergo nonsense-mediated decay, and classified as pathogenic according to ACMG criteria. Molecular confirmation enabled genetic counseling, cascade testing, withholding BCG, and urgent evaluation for allogeneic hematopoietic stem-cell transplantation. This case, likely the first CIITA-related MHC II deficiency reported from Morocco, expands the regional genotypic spectrum and underscores the value of early HLA-DR flow-cytometric assessment and prompt molecular testing in infants from consanguineous families to guide prophylaxis, vaccination decisions, and timely referral for curative therapy.